Recent Progress Of Graphene-Based Materials For Efficient Charge Transfer And Device Performance Stability In Perovskite Solar Cells - Mohd Abid, Mohd Asyadi 'Azam; Safie, Nur Ezyanie; Abdul Aziz, Mohd Fareezuan; Ismail, Mashasriyah (John Wiley and Sons Ltd, 2021)
The relevance of graphene-based materials throughout the niche area of perovskite solar cells (PSCs) is indeed the main focus of this review. Specific properties of two types of solar cell materials, namely hybrid perovskites and graphene-based materials are at the core of significant breakthroughs in a wide range of applications. The specific features of graphene-based materials, along with their unique properties, have been utilized mainly in the development of photovoltaic devices. PSCs are known to have promising device performance and surpass other third-generation solar cells, including organic photovoltaics, quantum dot solar cells, and dye-sensitized solar cells. However, PSCs address several limitations in the device mechanism and material stability. PSCs performance tends to deplete over time due to several factors such as the degradation of materials used in the device caused by exposure of thermal and moisture, as well as an undesired chemical reaction in the interfaces. Several experimental studies, especially on the integration of carbon materials, including the graphene, have been extensively explored. The integration of graphene-based materials is one of the potential methods for altering and modifying components in PSCs, including perovskite structure and charges transport layers. Therefore, this review gives an overview of recent progress in the development of PSCs with the integration of graphene-based materials. The emphasis will be on the influence brought by graphene-based materials on the charge transport mechanism at the interfaces and perovskite morphology toward the improvement of photovoltaic performance and stability